Наближені методи розв’язування диференціальних ігор із випадковим збуренням - Ostapenko, V. V.; Ostapenko, E. V.; Amirgalieva, S. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Differential games in which the role of the second player is played with a casual noise are investigated. The methods are developed, allowing to approximate guaranteed prizes of players and to build the appropriate strategy. For a substantiation of methods the concept of almost convex function is entered and investigated.